(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Currently, the fields of nanoelectronics, optoelectronics and photonics are developing rapidly. In these areas, the creation of effective working materials is an important task. Traditional Si&Ge based semiconductors are not suitable for photonics because they have an indirect energy gap.